2013
DOI: 10.1080/07391102.2013.785920
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based design and experimental engineering of a plant virus nanoparticle for the presentation of immunogenic epitopes and as a drug carrier

Abstract: Biomaterials research for the discovery of new generation nanoparticles is one of the most active areas of nanotechnology. In the search of nature-made nanometer-sized objects, plant virus particles appear as symmetrically defined entities that can be formed by protein self-assembly. In particular, in the field of plant virology, there is plenty of literature available describing the exploitation of plant viral cages to produce safe vaccine vehicles and nanoparticles for drug delivery. In this context, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…First, their external surfaces can be modified or decorated with other molecules, in which case VNPs can act as biocompatible nanocarriers for antigen presentation, immunomodulation, customized targeting, etc., as exemplified by the plant-infecting cowpea mosaic virus (CPMV, Chatterji et al, 2004;Lewis et al, 2006;Sainsbury et al, 2010;Steinmetz et al, 2011), tobacco mosaic virus (TMV, Alonso et al, 2013) or cowpea chlorotic mottle virus (CCMV, Suci et al, 2007). Second, as self-assembled cages, the inner cavity of VNPs can be used to encapsulate or encage a variety of active molecules, including pharmaceuticals, image enhancers and nucleic acids (Arcangeli et al, 2014;Bruckman et al, 2013;Mueller et al, 2011;Shriver et al, 2013). By acting on both external surface and inner cavity, VNPs can be adapted theoretically at will and are therefore regarded as extremely versatile tools with great potentials in medicine, as enzyme nanocarriers or even as novel biomaterials (for review, see Reference Alonso et al, 2013;Cardinale et al, 2012;Pokorski and Steinmetz, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…First, their external surfaces can be modified or decorated with other molecules, in which case VNPs can act as biocompatible nanocarriers for antigen presentation, immunomodulation, customized targeting, etc., as exemplified by the plant-infecting cowpea mosaic virus (CPMV, Chatterji et al, 2004;Lewis et al, 2006;Sainsbury et al, 2010;Steinmetz et al, 2011), tobacco mosaic virus (TMV, Alonso et al, 2013) or cowpea chlorotic mottle virus (CCMV, Suci et al, 2007). Second, as self-assembled cages, the inner cavity of VNPs can be used to encapsulate or encage a variety of active molecules, including pharmaceuticals, image enhancers and nucleic acids (Arcangeli et al, 2014;Bruckman et al, 2013;Mueller et al, 2011;Shriver et al, 2013). By acting on both external surface and inner cavity, VNPs can be adapted theoretically at will and are therefore regarded as extremely versatile tools with great potentials in medicine, as enzyme nanocarriers or even as novel biomaterials (for review, see Reference Alonso et al, 2013;Cardinale et al, 2012;Pokorski and Steinmetz, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on the structurally related Tombusvirus, Tomato bushy stunt virus (TBSV), showed that peptides could be fused to the C-terminus of the coat protein so that they are expressed on the P domain without abolishing virus or VLP assembly (Joelson et al, 1997 ; Kumar et al, 2009 ). The neutralizing HIV-1 2F5 epitope was recently expressed on Artichoke mottled crinkle virus surface, a virus also of the Tombusvirus genus (Arcangeli et al, 2014 ). We therefore decided to investigate whether it would be possible to present whole proteins, as opposed to peptides, on the surface of plant-expressed TCV VLPs.…”
Section: Resultsmentioning
confidence: 99%
“…Papaya mosaic virus nanoparticles that have been fused or conjugated with antigenic peptides have triggered immunogenic responses in mammals [5,10,24,25]. Over the past decade, various virus nanoparticles have been generated against different diseases [6].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that achieving an efficient virus nanoparticle for vaccine production requires a safe expression system in which large quantities of the desired protein can be easily produced [6]. Even though physiochemical and structural properties of virus nanoparticles highly affect their efficacy, the significance of a well-designed platform should never be neglected [25]. We, therefore, examined the immunogenicity Fig.…”
Section: Discussionmentioning
confidence: 99%